PENGARUH PENGGUNAAN MATERNITY BELT TERHADAP PENURUNAN DERAJAT NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER II - Fathi, Muhammad; Sisybania, Sisybania; Akbar, Muh Syaiful (Tahta Media Group, 2024)
Background: Pregnancy begins at conception and lasts until childbirth. During this period, pregnant women experience both psychological and physical changes that can lead to back pain. The initial cause of back pain is the forward growth of the uterus, which shifts the center of gravity of the earth towards the lower body. To help alleviate back pain in pregnant women, a maternity belt can be used to increase lumbopelvic stability by simultaneously pressing on the sacroiliac joint surface and positioning the sacroiliac joint in a specific position to enhance stability. In this research, before and after the intervention, the level of pain will be measured using the Numeric Rating Scale (NRS). Objective: to determine whether the level of back pain in second-trimester pregnant women decreases after using a maternity belt. Method and Subjects: This study is a quasi-experiment with a pre-test and post-test design. Samples were chosen using purposive sampling. The research instrument used the Numeric Rating Scale (NRS) and was analyzed using the Wilcoxon test with SPSS. Results: The pain scale before using the maternity belt had a minimum value of 3 (mild pain), a maximum value of 6 (moderate pain) with an average of 4.44 (moderate pain), whereas the pain scale after using the maternity belt had a minimum value of 1 (mild pain), a maximum value of 2 (mild pain) with an average of 1.32 (mild pain). Conclusion: There is an effect of using a maternity belt on the reduction of the degree of pain before and after using the maternity belt by 3.12 where p=0.000 (p<0.05)